Phenotypic plasticity and constraint along the upper and lower limb diaphyses of Homo sapiens. Issue 3 (5th November 2015) - Nadell, Jason A.; Shaw, Colin N.
ABSTRACT: Objectives: Morphological variation along the human limb reflects complex structural trade‐offs between bone strength and mass. Here we assess how varying levels of plasticity and constraint affect this structure and influence the response to habitual loading along the diaphysis. Materials and Methods: Cross‐sectional geometric properties including total area, cortical area, and rigidity were compared from the upper (humerus: 50% of length, radius: 66%, 50%, 4%) and lower (tibia: 50%, 38%, 4%) limbs of male varsity‐level athletes and matched controls with distinct habitual loading histories. Results: Geometric properties among cricketers and swimmers were significantly greater at the humeral midshaft, mid‐proximal radius, and radial midshaft compared to controls. By contrast, no significant differences were found among athletes or controls at the distal radius. The tibial midshafts of hockey players and runners also displayed greater area and rigidity compared to controls. Differences in geometry among the three groups became less pronounced distally, where structure was comparable among athletes and controls at 4% of tibial length. Additionally, coefficients of variation revealed that variation among athletes of the same sport was highest distally in both the upper and lower limb and lowest at midshaft, where structure most closely reflected the activity pattern of each loading group. Discussion: These results support previous research suggesting that distal limb sections are more tightly constrained by safety factors compared to midshafts and proximal sections. Overall, it appears that plasticity and constraint vary not only between limb segments in correspondence to known activity patterns, but also along specific sections of the diaphysis. Am J Phys Anthropol 159:410–422, 2016. © 2015 Wiley Periodicals, Inc.